Sharing and reuse of nursing research data: Necessary questions in preparing an interview instrument (Research, Society and Development, 2023)
Nursing has a plenty of scope of action, its data isn't produced only in the care process, but it is produced also in management, teaching, research and extension. Due to the diversity, irregular data patterns and different ways of sharing can appear. The interest in understanding how researchers in the area of ​​Nursing have sought to share and reuse their research data outlines the objective of this study: to present a process for developing an interview instrument on practices for sharing and reusing research data, aiming at its application to nursing researchers. This is an integrative review of interview instruments and questionnaires regarding the sharing and reuse of research data. As the possibility of sharing and reusing data is one of the pillars of Open Science and the management of this data is extremely important, the simple interview script can be followed by other researchers based on the proposal of this study. The elaboration of the interview instrument based on a structured search and questions based on already published articles allows the interviewee to respond in a reflective, participative and continuous way.